UNIMINUTO : Bringing Entrepreneurship, Innovation and Jobs to Marginalized Communities in Colombia through Tertiary Education - Casanova, Ann M. (International Finance Corporation, Washington, DC, 2016)
International Finance Corporation (IFC), a member of the World Bank Group, is the largest global development institution focused exclusively on leveraging the power of the private sector to tackle the world’s most pressing development challenges. Working with private enterprises in more than one hundred countries, IFC uses its capital, expertise and influence to help eliminate extreme poverty and promote shared prosperity. Expanding access to quality and affordable education is a central element to eliminate poverty and reduce inequality. In developing countries, private education providers play a critical role in the delivery of education, skills, and training that is affordable and relevant to the needs of the labor markets. The IFC education practice is developing four case studies that showcase success stories in the IFC education portfolio around scale, skills, affordability, and innovation. This case study highlights how IFC clients have contributed to meeting IFC’s strategic goals in education of: (1) developing skills and enhancing employability of graduates and trainees and (2) increasing reach and impact at all levels of education.